Higher Education for Sustainability in the Developing World: A Case Study of Rafik Hariri University1 in Lebanon - Hammoud, Jamil; Tarabay, Mohamed (European Journal of Sustainable Development, 2019)
Responding to heightened global interest in and concern for the sustainability of the planet and our ways of life on it, The United Nations’ Transforming Our World: The 2030 Agenda for Sustainable Development (2015) came out as a very ambitious and historic global agreement. The agenda identified what have become known as the 17 Sustainable Development Goals (SDGs), along with their detailed targets to mobilize and guide global efforts toward ending poverty, fostering peace, safeguarding human rights and protecting the planet. Education for Sustainable Development forms part of Target 4.7 of Sustainable Development Goal 4, which seeks to “ensure that all learners acquire the knowledge and skills needed to promote sustainable development, including, among others, through education for sustainable development and sustainable lifestyles…” Departing from the Brundtland Commission’s (1987) definition of sustainable development as a paradigm of resource use that “meets the needs of the present without compromising the ability of future generations to meet their own needs,” universities have progressively been incorporating sustainability values, practices and initiatives into their activities, throughout the realm of what they do in teaching, research, administration and operational systems. Indeed, Commitment to sustainability at universities worldwide dates back to the 1980’s, with a number of landmarks and declarations such as the Magna Charta of European Universities (1988), and the Talloires Declaration of University Presidents for a Sustainable Future (1990). However, the debate so far has centered mostly on the rationale and reasoning for broad adoption, rather than the various actions to be undertaken by higher education institutions (HEIs). Moreover, Efforts and initiatives to integrate sustainability into higher education in the developing world have been ad-hoc, modest and small (Mohamedbhai 2012). We could only find a few research studies covering such efforts and initiatives anyways (Awuzie & Emuze, 2017; Bhat et al., 2017; Khalaf-Kairouz, 2012). This paper aims to describe sustainable practices of higher education institutions in the developing world, via a case study of Rafik Hariri University in Lebanon. The authors utilize the 12 Features of Sustainable Society, developed by the Forum for the Future (2003) as an analytical framework, based on the Five Capitals Model. The research instrument was a questionnaire derived from the 12 Features of a Sustainable Society and designed to identify the strategies, policies, values and practices pursued by the university to contribute to sustainable development. The outcome is a detailed level analysis into the ways in which a small institution of higher education in a developing country contributes to the betterment of the world via engagement in sustainability. Keywords Sustainability; Sustainable Development; Higher Education; Developing World; Higher Education for Sustainable Development; Rafik Hariri University; Lebanon; ESD; SDG; HESD